The Influence of Leadership and Knowledge Sharing on Employee Performance through the Quality of Human Resources in the Investment Office and One-Stop Integrated Services - Buyung Arma, Andi; Ansar, Ansar; Hasmin, Hasmin; Gunawan, Gunawan (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
This study aims to determine and analyze the Influence of Leadership, Knowledge Sharing and HR Quality on Employee Performance with the object of research at the Office of Industry and Trade. This research is quantitative research. Data analysis techniques using Path analysis. The results of the study by testing the hypothesis using the calculated t value and significance based on the Path analysis model, concluded that; (1) Leadership has a significant effect on Employee Performance, showing significant results with a path coefficient of 0.283 (positive) and a significance value (p-value) of 0.013 (less than 5%); (2) Knowledge Sharing has a significant effect on Employee Performance, showing significant results with a path coefficient of 0.254 (positive) and a significance value (p-value) of 0.027 (less than 5%); (3) Leadership has a significant effect on HR Quality, showing significant results with a path coefficient of 0.499 (positive) and a significance value (p-value) of 0.000 (smaller than 5%); (4) Knowledge Sharing has a significant effect on HR Quality, showing significant results with a path coefficient of 0.506 (positive) and a significance value (p-value) of 0.000 (smaller than 5%); (5) HR quality has a significant effect on Employee Performance, showing significant results with a path coefficient of 0.380 (positive) and a significance value (p-value) of 0.005 (smaller than 5%); (6) Leadership has a significant effect on Employee Performance through HR Quality showing significant results with a coefficient of 0.190 (positive) and a significance value (p-value) of 0.0092 (smaller than 5%); (7) Knowledge Sharing has a significant effect on Employee Performance through HR Quality, showing significant results with a coefficient of 0.192 (positive) and a significance value (p-value) of 0.0089 (smaller than 5%).